2016
DOI: 10.1002/bsl.2269
|View full text |Cite
|
Sign up to set email alerts
|

Altruistic Lying in an Alibi Corroboration Context: The Effects of Liking, Compliance, and Relationship between Suspects and Witnesses

Abstract: Police investigators, judges, and jurors are often very skeptical of alibi witness testimony. To investigate when and why individuals lie for one another, we conducted two studies in which witnesses' support of a false alibi was observed. We varied the level of social pressure exerted on witnesses and the level of affinity between suspect-witness pairs. During a study session purportedly intended to investigate dyadic problem-solving ability, a mock theft was staged. When questioned, participants were provided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
(71 reference statements)
0
3
0
Order By: Relevance
“…Hosch et al (2011) found that participants were more likely to believe an alibi witness when that witness was unrelated versus related to the defendant (also see Eastwood et al, 2016;. Furthermore, Marion and Burke (2017) found evidence that alibi witnesses were more willing to corroborate a known false alibi for a friend than for a stranger, offering further support for Olson and Wells' taxonomy.…”
Section: A Alibis: a Review Of The Literature A Person Evidence And Physical Evidencementioning
confidence: 85%
“…Hosch et al (2011) found that participants were more likely to believe an alibi witness when that witness was unrelated versus related to the defendant (also see Eastwood et al, 2016;. Furthermore, Marion and Burke (2017) found evidence that alibi witnesses were more willing to corroborate a known false alibi for a friend than for a stranger, offering further support for Olson and Wells' taxonomy.…”
Section: A Alibis: a Review Of The Literature A Person Evidence And Physical Evidencementioning
confidence: 85%
“…One lab study confirmed that in fact people are more likely to lie for friends than strangers. In this study, participants had the opportunity to lie about an alibi for either a friend or stranger (Marion & Burke, 2017). Participants were much more likely to lie and say they were with the other participant when that person was a friend rather than a stranger.…”
Section: Introductionmentioning
confidence: 99%
“…Participants were much more likely to lie and say they were with the other participant when that person was a friend rather than a stranger. The participants stated that they liked their friends and trusted that they had not stolen the missing money from the lab when they were suspected of doing so (Marion & Burke, 2017). Thus, altruism and liking can explain why people help friends and family more often than strangers, and why judges, jurors and police officers are sceptical of alibi evidence from these sources.…”
Section: Introductionmentioning
confidence: 99%